2022
DOI: 10.1371/journal.pone.0274085
|View full text |Cite
|
Sign up to set email alerts
|

Breed-specific values for vertebral heart score (VHS), vertebral left atrial size (VLAS), and radiographic left atrial dimension (RLAD) in pugs without cardiac disease, and their relationship to Brachycephalic Obstructive Airway Syndrome (BOAS)

Abstract: This prospective study aims to establish reference ranges for vertebral heart score (VHS), vertebral left atrial size (VLAS), and radiographic left atrial dimension (RLAD) in pugs. The impact of clinical severity of Brachycephalic Obstructive Airway Syndrome (BOAS), gender, body condition score, and body weight on VHS, VLAS, and RLAD were investigated. Intra- and interobserver correlation was determined. Correlation of radiographic scores to echocardiographic left atrial dimension was inspected. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
10
2
Order By: Relevance
“…These methods were used to evaluate the heart size, focusing on the left atrial dimension, which is commonly enlarged secondary to degenerative mitral valve disease. It has been reported that Cavalier King Charles Spaniels [ 35 ], Chihuahuas [ 19 ], Maltese [ 11 ], and Pug-specific VLAS [ 7 ] have a lower value than the original value reported by Malcolm [ 9 ]. Therefore, the LA assessment using these two techniques should be warranted if there is a variation in the thoracic vertebral characteristics indicated by the T4L/H ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods were used to evaluate the heart size, focusing on the left atrial dimension, which is commonly enlarged secondary to degenerative mitral valve disease. It has been reported that Cavalier King Charles Spaniels [ 35 ], Chihuahuas [ 19 ], Maltese [ 11 ], and Pug-specific VLAS [ 7 ] have a lower value than the original value reported by Malcolm [ 9 ]. Therefore, the LA assessment using these two techniques should be warranted if there is a variation in the thoracic vertebral characteristics indicated by the T4L/H ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Several objective methods, such as the cardiothoracic ratio (CTR), cardiac size-to-intercostal space, and vertebral heart score (VHS), have been proposed. In addition, the radiographic left atrial dimension (RLAD) [ 6 , 7 , 8 ] and vertebral left atrial size (VLAS) [ 7 , 8 , 9 , 10 , 11 ] were recently proposed to evaluate the left atrial size on the thoracic radiograph. The CTR was adapted from human medicine [ 12 ] for use in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Both VLAS and VHS were measured to the nearest 0.1 vertebra. "Increased VLAS" was defined using published breed-specific reference intervals, [14][15][16][17] if available. If unavailable, VLAS >2.2 vertebrae defined increased VLAS.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was done using R version 4.0.4. Graphical analyses and data cleaning were done using ggplot2 and tidyverse (Wickham & RStudio 2017). PB regression, bootstrap confidence intervals and medical decision point analysis were done using the mcr package (Ekaterina Manuilova et al 2014).…”
Section: Softwarementioning
confidence: 99%
“…2021, Baisan & Vulpe 2022, Wiegel et al . 2022). The purpose of this study was to assess the performance of the use of a VHS algorithm utilising the simplified Sanchez method compared to manual VHS scoring on 1200 radiographs split between three board‐certified veterinary cardiologists using the Buchanan method.…”
Section: Introductionmentioning
confidence: 99%